Early Developmental Low-Dose Methylmercury Exposure Alters Learning and Memory in Periadolescent but Not Young Adult Rats - Albores-Garcia, Damaris (Biomed Res Int, 2016)
Few studies have assessed the effects of developmental methylmercury (MeHg) exposure on learning and memory at different ages. The possibility of the amelioration or worsening of the effects has not been sufficiently investigated. This study aimed to assess whether low-dose MeHg exposure in utero and during suckling induces differential disturbances in learning and memory of periadolescent and young adult rats. Four experimental groups of pregnant Sprague-Dawley rats were orally exposed to MeHg or vehicle from gestational day 5 to weaning: (1) control (vehicle), (2) 250 μg/kg/day MeHg, (3) 500 μg/kg/day MeHg, and (4) vehicle, and treated on the test day with MK-801 (0.15 mg/kg i.p.), an antagonist of the N-methyl D-aspartate receptor. The effects were evaluated in male offspring through the open field test, object recognition test, Morris water maze, and conditioned taste aversion. For each test and stage assessed, different groups of animals were used. MeHg exposure, in a dose-dependent manner, disrupted exploratory behaviour, recognition memory, spatial learning, and acquisition of aversive memories in periadolescent rats, but alterations were not observed in littermates tested in young adulthood. These results suggest that developmental low-dose exposure to MeHg induces age-dependent detrimental effects. The relevance of decreasing exposure to MeHg in humans remains to be determined.